Positive electrode material, preparation method and lithium ion battery
By preparing a cathode material with the general chemical formula LixNiaCobMcNdO2, and controlling the content and doping level of free SO42- during the preparation process, the problems of poor rate performance and cycle stability of existing cathode materials are solved, and better electrochemical performance is achieved. chemical properties.
Patent Information
- Application Number
- CN202411935345.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-12-26
AI Technical Summary
The current cathode materials have poor rate performance and cycle stability.
By preparing the positive electrode material of LixniacobMCNDO2, the content of free SO42- ≤800ppm is controlled, and some SO42-doped into the internal lattice during the preparation process to inhibit the contraction of the C-axis and reduce the activation energy of li migration.
Improve the cycle performance and multiplier performance of the positive pole material, and improve the structural stability and electrochemical properties of the material.
Smart Images

Figure CN119361683A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of positive electrode materials, and in particular to a positive electrode material, a preparation method thereof, and a lithium ion battery. Background Art
[0002] Positive electrode materials have high energy density and are one of the mainstream positive electrode materials for power lithium batteries. They are widely used in mid-to-high-end new energy vehicles. Positive electrode materials are usually prepared by high-temperature sintering of precursor compounds containing Ni, Co and Mn and lithium salts. However, the existing positive electrode materials have poor rate performance and cycle stability.
[0003] In view of this, this application is hereby filed. Summary of the invention
[0004] The main purpose of the present invention is to provide a positive electrode material precursor, a positive electrode material and a preparation method and a lithium ion battery, so as to solve the problem of poor rate performance and cycle stability of the positive electrode material in the prior art.
[0005] In order to achieve the above object, according to the first aspect of the present invention, a positive electrode material is provided, the chemical formula of which is Li x Ni a Co b M c N d O2, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, 0≤d≤0.10, a+b+c+d=1, the M element includes at least one of Mn or Al, the N element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y, and the free SO4 of the positive electrode material 2- The content of SO4 is ≤800ppm, and SO4 2- The surface enrichment is ≤70%.
[0006] According to the second aspect of the present invention, a method for preparing a positive electrode material is also provided, the preparation method comprising: atomizing and pyrolyzing a mixed solution of metal salts containing Ni salt, Co salt, Mn salt and N salt in sequence to obtain a positive electrode material precursor; mixing the positive electrode material precursor and a lithium source and sintering them to obtain a positive electrode material; wherein the general formula of the positive electrode material precursor is Ni a Co b Mn c N d O e, wherein, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.35, 0≤d≤0.10, a+b+c+d=1, 1≤e≤1.15, N element, N includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y; the chemical formula of the positive electrode material is Li x Ni a Co b Mn c N d O2, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, 0≤d≤0.10, a+b+c+d=1, and the N element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y; the free SO4 of the positive electrode material 2- The content of SO4 is ≤800ppm, and SO4 2- The surface enrichment is ≤70%.
[0007] According to a third aspect of the present invention, a lithium-ion battery is further provided, the lithium-ion battery comprising the positive electrode material provided in the first aspect or the positive electrode material obtained according to the preparation method provided in the second aspect.
[0008] By applying the technical solution of this application, the free SO4 2- The content of SO4 is ≤800ppm, and SO4 2- The surface enrichment of SO4 is ≤70%; some SO4 2- Doping into the internal lattice, SO4 in the bulk 2- It can inhibit the contraction of the c-axis, reduce the activation energy of Li migration, thereby increasing the migration rate of Li, inhibit heterogeneous reactions, and reduce lattice rotation, thereby improving the cycle performance and rate performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0010] Figure 1 shows a Williamsone-Hall analysis fitting curve of the positive electrode material according to Example 1 of the present invention;
[0011] Figure 2 A SEM image of the positive electrode material according to Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0012] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0013] As described in the background of the present application, the existing positive electrode materials have poor rate performance and cycle stability. In order to solve this problem, the present application provides a positive electrode material and a preparation method thereof and a lithium ion battery.
[0014] In a first typical embodiment of the present application, a positive electrode material is provided, the chemical formula of which is Li x Ni a Co b M c N d O2, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, 0≤d≤0.10, a+b+c+d=1, the M element includes at least one of Mn or Al, and the N element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y; the free SO4 of the positive electrode material 2- The content of SO4 is ≤800ppm, and SO4 2- The surface enrichment is ≤70%.
[0015] In this application, SO4 2- The surface enrichment refers to the free SO4 2- Content and SO4 in positive electrode materials 2- The ratio of total content.
[0016] Free SO4 in cathode material 2- It has a great influence on the electrochemical properties of the material. When free SO4 2- When the content is high, the material capacity and rate will deteriorate. The free SO4 2- The content of SO4 is ≤800ppm, and SO4 2- The surface enrichment of SO4 is ≤70%, indicating that part of SO4 2- Doping into the internal lattice, SO4 in the bulk 2- It can inhibit the contraction of the c-axis, reduce the activation energy of Li migration, thereby increasing the migration rate of Li, inhibit heterogeneous reactions, and reduce lattice rotation, thereby improving the cycle performance and rate performance of the positive electrode material.
[0017] Typically but not limiting, in the positive electrode material provided in the present application, the value of x can be 0.98, 0.99, 1.0, 1.01, 1.03, 1.05, 1.08, 1.09, 1.1 or a range of any two values; the value of a can be 0.50, 0.55, 0.60, 0.63, 0.70, 0.75, 0.80, 0.85, 0.88, 0.90, 0.95, 0.98 or a range of any two values; the value of b can be 0.01, 0.05, 0.08, 0.10, 0.11, 0.13, 0.15, 0.18, 0.20 or any two values in the range; c can be 0.01, 0.05, 0.10, 0.15, 0.18, 0.20, 0.23, 0.27, 0.30 or any two values in the range; d can be 0, 0.01, 0.03, 0.05, 0.06, 0.07, 0.08, 0.09, 0.10 or any two values in the range; free SO4 2- The content of SO4 is 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 550ppm, 600ppm, 650ppm, 700ppm, 750ppm, 800ppm or a range consisting of any two values; 2- The surface enrichment is 10%, 20%, 30%, 40%, 50%, 55%, 60%, 65%, 70% or a range consisting of any two values.
[0018] In some embodiments, under a pressure of 6T for the positive electrode material, the volume proportion of particles below 1 μm is ≤4%, and there is an appropriate amount of micropowder in the positive electrode material, which can be filled in the gaps between the particles to improve the cycle stability. If the volume proportion of particles below 1 μm in the positive electrode material is too high, the content of micropowder in the positive electrode material is too much, the specific surface area of the micropowder is too large, and the solution and the electrolyte react, thereby affecting the cycle stability. Specifically, under a pressure of 6T for the positive electrode material, the volume proportion of particles below 1 μm is 0, 0.1%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, or a range of any two values.
[0019] In some embodiments, the lattice strain of the positive electrode material is ≤0.2%, so as to improve the structural stability of the positive electrode material, reduce the probability of particle cracking during the cycle, and thus improve its cycle stability. Specifically, the lattice strain of the positive electrode material can be 0.01%, 0.03%, 0.05%, 0.08%, 0.10%, 0.11%, 0.12%, 0.15%, 0.18%, 0.19%, 0.2, or a range of any two values.
[0020] In some embodiments, the positive electrode material further includes a coating layer, and the coating layer includes at least one element of Al, Ti, Zr, Y, Nb, Mg, W, B, Ce, Co, and Mn. Providing the coating layer is beneficial to reducing the direct contact between the positive electrode material and the electrolyte, reducing the occurrence of side reactions between the positive electrode material and the electrolyte, and improving the cycle performance, rate performance, and DCR (direct current internal resistance).
[0021] In some embodiments, the particle size D50 of the positive electrode material is 2.5 μm-5 μm, so as to improve the compaction density of the positive electrode, thereby improving its electrochemical performance. Specifically, the volume distribution D50 of the positive electrode material precursor can be 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm, 5.0 μm, or a range of any two values.
[0022] In some embodiments, the particle size Dmin of the positive electrode material is greater than 0.3 μm. The smaller the particle size of the positive electrode material, the more conducive it is to improving its particle strength. However, if the particle size of the positive electrode material is too small, it is not conducive to improving its electrochemical performance. Specifically, the volume distribution Dmin of the positive electrode material precursor can be 0.35 μm, 0.40 μm, 0.45 μm, 0.50 μm, 0.55 μm, 0.6 μm, or a range of any two values.
[0023] In some embodiments, the particle size Dmax of the positive electrode material is less than 14 μm. If the particle size of the positive electrode material is too large, it is not conducive to improving its compaction density, and thus not conducive to improving its electrochemical performance. Specifically, the volume distribution Dmax of the positive electrode material precursor can be 13,9 μm, 13 μm, 12 μm, 11 μm, 10 um, 9 um, or a range of any two values.
[0024] In some embodiments, the specific surface area of the positive electrode material is 0.5-1.2 m 2 / g. If the specific surface area of the positive electrode material is too large, its electrochemical performance is poor. If the specific surface area of the positive electrode material is too small, it is not conducive to improving its compaction density. Therefore, selecting a positive electrode material with an appropriate specific surface area is more conducive to improving the electrochemical performance of the positive electrode material. Specifically, the specific surface area of the positive electrode material can be 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g or a range of any two values.
[0025] In some embodiments, the pH of the positive electrode material satisfies 11.0≤pH≤12.0. If the pH of the positive electrode material is too low, it is not conducive to stable dispersion in the slurry. If the pH of the positive electrode material is too high, the alkalinity is too high, which is not conducive to improving the stability of the positive electrode sheet. Specifically, the pH of the positive electrode material can be 11.0, 11.2, 11.5, 11.8, 12.0, or a range of any two values.
[0026] In some embodiments, the positive electrode material is a single crystal material, and the positive electrode material includes grains with the same orientation, and the grain size of the grains is 1μm-5μm, so as to improve the stability of the positive electrode material during the cycle, reduce the probability of cracking, and thus improve its cycle stability. Specifically, the grain size can be 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 4μm, 5μm, or a range of any two values.
[0027] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that polycrystalline secondary particles are secondary particles formed by the agglomeration of nanoscale primary particles. Single crystal positive electrode materials are usually single primary particles of micrometer scale. Generally speaking, SEM, EBSD and other testing methods can be used to determine whether the obtained positive electrode product is a single crystal material. For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM; single crystal particles under SEM generally appear as regular or irregular spheres, and there is no significant particle agglomeration. EBSD can usually be used to characterize the orientation of the crystal structure. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that most of the grains of single crystal positive electrode materials have the same color, indicating that most of the grains are single primary particles with the same orientation. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.
[0028] In a second typical embodiment of the present application, a method for preparing a positive electrode material is also provided, the preparation method comprising: step S1, adding an appropriate amount of H2SO4 to a metal salt mixed solution containing Ni salt, Co salt, Mn salt and N salt for mixing to obtain a mixed solution; step S2, atomizing and pyrolyzing the mixed solution to obtain a pyrolyzed positive electrode material precursor; step S3, mixing the positive electrode material precursor and a lithium source for sintering to obtain the positive electrode material; the general formula of the positive electrode material precursor is Ni a Co bMn c N d O e , wherein 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.35, 0≤d≤0.10, a+b+c+d=1, 1≤e≤1.15, N is a doping element, and N includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y; the general chemical formula of the positive electrode material is Li x Ni a Co b M c N d O2, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, 0≤d≤0.10, a+b+c+d=1, the M element includes at least one of Mn or Al, and the N element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y; the free SO4 of the positive electrode material 2- The content of SO4 is ≤800ppm, and SO4 2- The surface richness is ≤70%.
[0029] Therefore, the present invention adds a certain amount of H2SO4 to the positive electrode material precursor during the preparation process, so that part of the SO4 2- Will be doped into the bulk phase, thereby preparing free SO4 2- The content of SO4 is ≤800ppm, and SO4 2- The surface enrichment of the positive electrode material is ≤70%, which improves the cycle performance and rate performance of the positive electrode material.
[0030] In some embodiments, in the metal salt mixed solution, the molar ratio of Ni element, Co element, M element and N element is (50-98): (0-20): (0-35): (0-0.10), and the Co element and the M element are not 0. Specifically, in the metal salt mixed solution, the molar ratio of Ni element, Co element and M element can be 50:0.1:0.1, 60:10:30, 65:15:20, 65:5:30, 70:5:25, 70:10:20, 80:5:15, 85:10:5, 98:1:1 or a range consisting of any two values. The molar ratio of Ni element, Co element, M element and N element can be 50:0.1:0.1:0.01, 60:10:30:0.02, 65:15:20:0.05, 65:5:30:0.08, 70:5:25:0.1, 70:10:20:0.1, 80:5:15:0.01, 85:10:5:0.1, 98:1:1:0.05 or a range value consisting of any two numerical values.
[0031] In some embodiments, in the metal salt mixed solution, the total metal concentration is 100 g / L-500 g / L, wherein the total metal includes Ni, Co, M and N. Specifically, in the metal salt mixed solution, the total metal concentration can be 200 g / L, 220 g / L, 260 g / L, 300 g / L, 350 g / L, 400 g / L, 450 g / L, 480 g / L, 500 g / L or a range consisting of any two values.
[0032] In some embodiments, in the metal salt mixed solution, based on the total mass of Ni element, Co element, Mn element, and N element, SO4 2- The content of SO4 is ≤2400ppm. Specifically, in the metal salt mixed solution, SO4 2- The content can be 2400 ppm, 2300 ppm, 2200 ppm, 2100 ppm, 2000 ppm, 1800 ppm, 1500 ppm, 1300 ppm, 1100 ppm, 800 ppm or a range consisting of any two values.
[0033] In step S2, the mixed solution is atomized by a plasma rotating electrode to form micronized droplets of 2 to 200 μm in size, which are then pyrolyzed into a calcining furnace to prepare a precursor. By controlling the size of the atomized droplets, the droplets are atomized to form precursor particles with a moderate particle size, which is beneficial to SO4 2- Doping into the interior of the crystal lattice.
[0034] In some embodiments, the pressure of the atomization treatment is 0.4 MPa-0.8 MPa. Specifically, the pressure of the atomization treatment can be 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.75 MPa, 0.8 MPa or a range consisting of any two values.
[0035] In step S2, the atomized droplets pass through two temperature zones of the roasting furnace in sequence. The temperature of the first temperature zone is 1000-1200°C. The material stays in this temperature zone for 2-10 seconds to prevent the precursor particles from growing too large and affecting the reaction activity of the precursor. The short high temperature can promote the doping of S. The second temperature zone has a pyrolysis temperature of 500-800°C, which promotes the further decomposition of the metal salt to form an oxide precursor.
[0036] The size of the precursor particles is related to the pyrolysis temperature of the first temperature zone. The higher the temperature, the larger the precursor particles. In some embodiments, in step S2, the temperature of the first temperature zone is controlled to be 1000-1200°C, and the residence time is 2-10s to facilitate the pyrolysis of precursor particles with a moderate particle size, which is also more conducive to SO4 2- The doping enters the interior of the crystal lattice. Specifically, the pyrolysis temperature of the first temperature zone can be controlled to be 1000°C, 1020°C, 1050°C, 1080°C, 1200°C or a range consisting of any two values.
[0037] When the temperature in the first temperature zone is too high, the particle size of the precursor particles formed is too large, the particle strength of the prepared positive electrode material is low, and the lattice strain is large. When the temperature is too low, SO4 2- It is difficult to dope into the interior of the crystal lattice.
[0038] SO4 2- Due to the large ionic radius, it is very difficult to dope into the lattice of the precursor or the positive electrode material in the actual synthesis process. In the present invention, the applicant has found through a large number of experiments that by controlling the O2 content of the roasting furnace to ≤12%, the SO4 2- The surface enrichment of SO4 is significantly reduced; the possible reason may be that when the volume content of O2 is ≤15%, a reducing atmosphere is easily formed in the roasting furnace. In a reducing atmosphere, some SO4 2- can be reduced to S 2- Low-valent ions such as O2 can more easily enter the lattice inside the cathode material precursor. Specifically, in the pyrolysis atmosphere, the volume content of O2 can be 0, 1%, 2%, 5%, 8%, 9%, 10%, 11%, 12%, or a range consisting of any two values.
[0039] In some embodiments, the specific type of lithium source is not limited, and any commonly used lithium-containing compound in the art can be used, including but not limited to at least one of lithium carbonate, lithium hydroxide, lithium acetate, lithium sulfate, lithium chloride, lithium nitrate and lithium oxalate.
[0040] In some embodiments, the molar ratio of the lithium element in the lithium source to the total metal in the positive electrode material precursor is 0.98-1.10; wherein the molar amount of the total metal in the positive electrode material precursor is the sum of the molar amounts of the Ni element, the Co element, the Mn element, and the N element in the positive electrode material precursor. Specifically, the molar ratio of the lithium element in the lithium source to the total metal in the positive electrode material precursor is 0.98, 0.99, 1.01, 1.03, 1.05, 1.06, 1.08, 1.09, 1.10, or a range of any two values.
[0041] In some embodiments, in step S3, the sintering atmosphere is an oxygen-containing atmosphere, and the volume content of O2 is ≥95%, so as to provide an oxidizing atmosphere, oxidize and sinter the positive electrode material precursor and the lithium source, and prepare a positive electrode material with a more stable layered structure. Specifically, in the sintering atmosphere, the volume content of O2 can be 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 99%, 100%, or a range of any two values.
[0042] In some embodiments, in step S3, the sintering temperature is 750-980°C, and the sintering time is 10h-30h, so as to reduce the crystal structure defects of the positive electrode material, reduce the lattice strain, control the particle size distribution, and thus improve the electrochemical performance of the positive electrode material. Specifically, the sintering temperature can be 750°C, 760°C, 780°C, 800°C, 850°C, 900°C, 920°C, 950°C, 980°C, or a range of any two values; the sintering time can be 10h, 12h, 15h, 16h, 18h, 20h, 24h, 28h, 30h, or a range of any two values.
[0043] In a third typical embodiment of the present application, a lithium-ion battery is further provided. The lithium-ion battery comprises the positive electrode material provided in the first typical embodiment or the positive electrode material obtained by the preparation method provided in the second typical embodiment.
[0044] The lithium-ion battery provided in this application uses free SO4 2- The content of SO4 is ≤800ppm, and SO4 2- The positive electrode material with a surface enrichment of ≤70% has excellent cycle performance and rate performance.
[0045] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.
[0046] Example 1
[0047] This embodiment provides a positive electrode material, which is prepared according to the following steps:
[0048] (1) In molar ratio (n Ni :n Co :n Mn =0.60:0.1:0.3) Weigh nickel nitrate, cobalt nitrate, and manganese nitrate and add them into water to prepare a metal salt mixed solution. Control the total metal concentration in the metal salt mixed solution to be 300g / L. Add H2SO4 to adjust the SO4 in the mixed solution. 2- The mass ratio relative to the total metal is 1200 ppm, wherein the mass of the total metal refers to the sum of the masses of the Ni element, the Co element and the Mn element in the metal salt mixed solution.
[0049] (2) After the metal salt mixed solution is atomized into droplets through a plasma rotating electrode, it is placed in a pyrolysis atmosphere and pyrolyzed in a first temperature zone and a second temperature zone in a roasting furnace. The solid obtained by pyrolysis is pulverized by air flow to obtain a positive electrode material precursor. The chemical formula of the positive electrode material precursor is Ni 0.60 Co 0.1 Mn 0.3 O; wherein, the volume concentration of O2 in the pyrolysis atmosphere is controlled to be 8%, and in the process of atomizing into droplets, the flow rate is controlled to be 200L / h, the atomization pressure is 0.6MPa, the heating temperature in the first temperature zone is: 1100°C, the material residence time is 5s, the heating temperature in the second temperature zone is 750°C, and the residence time is 60s.
[0050] (3) After the cathode material precursor and lithium hydroxide are mixed evenly, the mixture is placed in an oxygen atmosphere and heated to 930°C and sintered for 20 hours to obtain the cathode material LiNi 0.60 Co 0.1 Mn 0.3 O2. The molar ratio of lithium hydroxide to the total metal in the positive electrode material precursor is 1:1, and the molar amount of the total metal in the positive electrode material precursor refers to the sum of the molar amounts of Ni element, Co element and Mn element.
[0051] Example 2
[0052] The difference between this embodiment and embodiment 1 is that in step (1), in the metal salt mixed solution, SO4 2- The mass ratio relative to the total metal is 500 ppm.
[0053] Example 3
[0054] The difference between this embodiment and embodiment 1 is that in step (1), in the metal salt mixed solution, SO4 2- The mass ratio relative to the total metal is 1500 ppm.
[0055] Example 4
[0056] The difference between this embodiment and embodiment 1 is that in step (1), in the metal salt mixed solution, SO4 2- The mass ratio relative to the total metal is 900ppm, and in step (2), the heating temperature of the first temperature zone is 1000°C, the material residence time is 5s, the temperature of the second temperature zone is 750°C for pyrolysis, and the volume concentration of O2 in the pyrolysis atmosphere is 11%.
[0057] Example 5
[0058] The difference between this embodiment and embodiment 1 is that in step (2), the heating temperature of the first temperature zone is 1200°C, the material residence time is 9s, the temperature of the second temperature zone is 750°C for pyrolysis, and the volume concentration of O2 in the pyrolysis atmosphere is 5%.
[0059] Example 6
[0060] The difference between this embodiment and embodiment 1 is that in step (1), in the metal salt mixed solution, SO4 2- The mass ratio relative to the total metal is 2400ppm. In step (2), the heating temperature of the first temperature zone is 1100°C, the material residence time is 5s, the temperature of the second temperature zone is 8750°C for pyrolysis, and the volume concentration of O2 in the pyrolysis atmosphere is 6%.
[0061] Example 7
[0062] The difference between this embodiment and embodiment 1 is that in step (2), the heating temperature of the first temperature zone is 1000°C, the material residence time is 2s, the temperature of the second temperature zone is 500°C, and the volume concentration of O2 in the pyrolysis atmosphere is 12%.
[0063] Example 8
[0064] The difference between this embodiment and embodiment 1 is that in step (1), the molar ratio of nickel, cobalt and manganese is n Ni :n Co :n Mn =0.90:0.05:0.05, in step (3), the sintering temperature is 750°C, the sintering time is 30h, and the sintering atmosphere is an oxygen-containing atmosphere with a volume concentration of O2 of 99%.
[0065] Example 9
[0066] The difference between this embodiment and embodiment 1 is that in step (1), the molar ratio of nickel, cobalt and manganese is n Ni :n Co :n Mn =0.55:0.10:0.25, in step (3), the sintering temperature is 980°C, the sintering time is 10h, and the sintering atmosphere is an oxygen-containing atmosphere with a volume concentration of O2 of 95%.
[0067] Example 10
[0068] The difference between this embodiment and embodiment 1 is that in step (1), the total metal concentration in the metal salt mixed solution is 100 g / L, and in step (2), the pressure of the atomization treatment is 0.4 MPa.
[0069] Embodiment 11
[0070] The difference between this embodiment and embodiment 1 is that in step (1), the total metal concentration in the metal salt mixed solution is 500 g / L, and in step (2), the pressure of the atomization treatment is 0.8 MPa.
[0071] Example 12
[0072] The difference between this embodiment and embodiment 8 is that in step (1), the molar ratio (n Ni :n Co :n Al =0.90:0.05:0.05) Weigh nickel nitrate, cobalt nitrate and aluminum nitrate and add them into water to prepare a metal salt mixed solution.
[0073] Comparative Example 1
[0074] The difference between this comparative example and Example 1 is that in step (2), the volume concentration of O2 in the pyrolysis atmosphere is 25%, and only the second temperature zone is set, and the heating temperature of the second temperature zone is 750°C.
[0075] Comparative Example 2
[0076] The difference between this comparative example and Example 1 is that in step (1), SO4 2- The mass ratio relative to the total metal is 650 ppm. In step (2), the volume concentration of O2 in the pyrolysis atmosphere is 25%, and only the second temperature zone is set, and the heating temperature of the second temperature zone is 750°C.
[0077] Comparative Example 3
[0078] The difference between this comparative example and Example 1 is that in step (1), SO4 2- The mass ratio relative to the total metals is 2900 ppm.
[0079] Comparative Example 4
[0080] The difference between this comparative example and Example 1 is that in step (2), the volume concentration of O2 in the pyrolysis atmosphere is 15%.
[0081] Comparative Example 5
[0082] The difference between this comparative example and Example 1 is that in step (2), the temperature of the first temperature zone is 1400° C., and the volume concentration of O 2 in the pyrolysis atmosphere is 15%.
[0083] Test Example 1
[0084] The positive electrode material precursors and positive electrode materials prepared in the examples and comparative examples were subjected to particle size D50, grain size, pH value, free SO4 2- Content, SO4 2- The total amount and surface enrichment were tested, and the results are shown in Table 1. In addition, the lattice strain of the positive electrode materials prepared in the embodiments and comparative examples was measured, and the results are shown in Table 1.
[0085] Wherein, (1) the particle size determination method is: using Malvern 3000 laser particle size analyzer to measure and obtain the average particle size D50 of the volume distribution of the positive electrode material precursor or the positive electrode material.
[0086] (2) The test method for grain size is as follows: prepare the cross-section sample using an ion cutting instrument, then use a Hitachi S4800 scanning electron microscope to test the cross-section morphology, and take 10 photos at a magnification of 5K. All pictures are imported into the software Nano Measure to count the size of the single crystal particles.
[0087] (3) The pH value test method is: use METTLER TOLEDO FE28 to test the pH of the positive electrode material. The specific process is as follows: take about 5g of positive electrode material sample, add 45mL of water, ultrasonicate for 5 minutes, take it out and let it stand for 10 minutes. After the pH meter is calibrated, the composite electrode is inserted into the upper clear liquid to be tested. The pH value of the solution is calculated based on the potential difference between the measuring electrode and the reference electrode.
[0088] (4) The method for determining lattice strain is: the lattice strain of the positive electrode material is calculated by Williamsone-Hall analysis from XRD data. The specific method is: using a Japanese Rigaku X-ray diffractometer for measurement, the specific conditions are: 0.75 degrees / minute, step size 0.02, continuous scanning between 10 and 90 degrees in the 2θ range. By drawing a 4sinθ hkl is the horizontal axis, β hkl cosθ hklAs the ordinate, draw a curve and linearly fit it, and the strain ε can be calculated by the slope. It is worth mentioning that the half-peak width βhkl used for fitting needs to eliminate the influence of the instrument, that is, βhkl=βtotal-βinstrument, where βtotal is the half-peak width value of the actual test, and βinstrument is the half-peak width broadening caused by the instrument, which can be obtained by XRD calculation of the test standard silicon wafer. The βinstrument of the test equipment used in this application is 0.000103. In addition, the data of the seven stronger diffraction peaks (003), (101), (102), (104), (015), (107), and (113) are selected for fitting to improve the degree of linear fitting and reduce the actual test error.
[0089]
[0090] Where β is the half-peak width, θ is the diffraction angle, both in radians; k is a constant, which is 0.89; λ is the X-ray wavelength, which is 0.154nm; D is the grain size, in nm; ε is the lattice strain, which is dimensionless.
[0091] (5) Volume ratio test of 1 μm positive electrode material particles under 6T pressure: 1 g of sample was placed in the mold of a compaction density meter (U.S. Carver 4350) and pressed with 6T pressure for 30s. The sample was then taken out and the volume ratio of particles under 1 μm was tested using a Malvern 3000 laser particle size analyzer.
[0092] (6) The method for determining the free anion content is as follows: take 0.5 g and dissolve it in 50 ml of water. After filtering with ultrasonic for 5 min, the filtrate is used to measure the free ion content of F / Cl / SO4 etc. by ion chromatography (Thermo Fisher Scientific ICS6000 HPIC).
[0093] (7) SO4 2- The total content was determined by taking a certain amount of sample and adding aqua regia to digest it. After cooling and settling, the content of S element was measured using Agilent 5110 ICP-OES and recorded as ms; SO4 2- Total content = ms × SO4 2- Molecular weight / molecular weight of S.
[0094] Table 1
[0095]
[0096] Figure 1 The Williamsone-Hall analysis fitting curve of the positive electrode material provided in Example 1 is shown. Figure 1It can be seen that there is a good linear relationship between βcosθ and 4sinθ. The lattice strain of the positive electrode material prepared in Example 1 is the slope of the fitted straight line, i.e., 0.1%, indicating that the lattice strain of the positive electrode material prepared in Example 1 is less than 0.2%.
[0097] Figure 2 The SEM image of the positive electrode material provided in Example 1 is shown. Figure 2 It can be seen that the positive electrode material prepared in Example 1 is mainly in the form of single crystal.
[0098] Test Example 2
[0099] The electrochemical performance of the positive electrode materials prepared in the above embodiments and comparative examples was evaluated by using a button half-cell. The specific method is as follows: the positive electrode material, conductive carbon black, and polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 93:5:2, N-methyl-2-pyrrolidone (NMP) was added at a solid content of 50%, and a high-speed disperser was used to adjust the viscous slurry. The slurry was evenly coated on an aluminum foil with a scraper, and after being dried in an oven at 80°C, the slurry was rolled and cut into a positive electrode sheet with a diameter of 14 mm. A 16 mm lithium sheet was used as the negative electrode sheet, a Celgard polypropylene film was used as the diaphragm, and a carbonate solution of LiPF6 with a concentration of 1 mol / L was used as the electrolyte. The assemblies were performed in a glove box filled with argon gas to obtain a button half-cell. The capacity and cycle performance tests were performed at 25°C and 3.0-4.4V (except for Example 8, whose voltage range was 3.0-4.3V) using a LAND battery test system, and the nominal capacity 2C was set to 200mAh / g. In addition, record the voltage U at the beginning of each week’s discharge A And the voltage data U at 60s B , discharge current I Dis The calculation formula of DC internal resistance is DCR = (U A -U B ) / I Dis The test results are shown in Table 2 below.
[0100] Table 2
[0101]
[0102] Combining Table 1 and Table 2, the free SO4 in Examples 1-12 of the present invention 2- The content of SO4 is ≤800ppm, and SO4 2- The surface enrichment of the positive electrode material provided by the present application is ≤70%, and its cycle performance and capacity are significantly better than those of comparative examples 1-4. 2- The content of SO4 is ≤800ppm, and SO4 2- The surface enrichment of SO4 is ≤70%, indicating that part of SO4 2-Doping into the internal lattice inhibits the contraction of the c-axis, reduces the activation energy of Li migration, and thus improves the cycle performance and rate performance of the positive electrode material, offsetting the free SO4 2- The negative impact caused.
[0103] Compared with Example 1, in Example 2, the amount of SO4 in the metal salt solution in step (1) is reduced. 2- The content of free SO4 in the prepared positive electrode material 2- The content has decreased, and SO4 2- The enrichment of SO4 remains basically unchanged, and the cycle performance and rate performance of the positive electrode material are good, indicating that at a certain amount of SO4 2- Based on doping, reducing free SO4 2- The content is beneficial to improving the electrochemical performance of the positive electrode material. In Example 3, the SO4 content of the metal salt solution in step (1) is increased. 2- Content, free SO4 2- Content and SO4 2- The enrichment of SO4 increased, but the cycle performance and rate performance of the positive electrode material decreased. 2- Excessive content will affect the cycle performance and rate performance of the positive electrode material.
[0104] Compared with Example 1, in Example 4, the SO4 content of the metal salt solution in step (1) is reduced. 2- The content of free SO4 in the cathode material is reduced by reducing the heating temperature and material residence time in the first temperature zone. 2- Content and SO4 2- The enrichment of free SO4 increased, and the cycle performance and rate performance of the positive electrode material were poor. 2- The content of SO4 is also reduced 2- The doping amount is not conducive to improving the electrochemical performance of the positive electrode material. In Example 5, the heating temperature of the first temperature zone is increased, and the material residence time in the first temperature zone is prolonged. The free SO4 2- The content decreased, while SO4 2- The enrichment of has increased, and the cycle performance and rate performance of the positive electrode material are good, indicating that reducing the free SO4 2- The content of SO4 is also increased 2- The doping amount can further inhibit the shrinkage of the c-axis, reduce the activation energy of Li migration, and thus improve the cycle performance and rate performance of the positive electrode material, offset the free SO4 2- The negative impact caused.
[0105] Compared with Example 1, in Examples 4-6, the heating temperature and material residence time of the first temperature zone were changed, and the volume proportion of particles under 1 μm at 6t of the obtained positive electrode material was changed. In Example 5, the heating temperature of the first temperature zone was 1200°C, the heating temperature of the first temperature zone was greater than the heating temperature in Examples 4 and 6, and the material residence time was 9s, and the material residence time was greater than the residence time in Examples 4 and 6. The volume proportion of particles under 1 μm at 6t of the obtained positive electrode material was 4%, and the obtained positive electrode material had good cycle performance and rate performance, indicating that the presence of a certain amount of micropowder can increase the cycle stability and rate performance of the positive electrode material.
[0106] In Comparative Examples 1 and 2, the volume concentration of O2 in the pyrolysis atmosphere was 25%, and only the second temperature zone was set, and the SO4 of the prepared positive electrode material 2- The surface enrichment of SO4 in the precursor solution is as high as 90%, indicating that 2- It is difficult to be restored to S 2- Low-valent ions such as SO4 2- It is difficult to dope into the bulk phase, resulting in SO4 2- The shrinkage of the c-axis cannot be suppressed, and the cycle performance and rate performance of the positive electrode material are poor.
[0107] In Comparative Example 3, the SO4 in the solution in step (1) 2- The concentration of is too high, and the prepared positive electrode material has free SO4 2- The content is 832ppm. During the circulation process, free SO4 2- It is easy to produce side reactions with the electrolyte, resulting in poor cycle stability of the positive electrode material. In Comparative Example 4, the volume concentration of O2 in the pyrolysis atmosphere is 15%. During the spray pyrolysis process, SO4 2- Difficult to restore to S 2- Low-valent ions such as SO4 2- It is difficult to dope into the bulk phase, SO4 of the positive electrode material 2- The enrichment of is high, resulting in poor cycle stability of the positive electrode material.
[0108] In comparative example 5, the temperature of the first temperature zone in step (2) is 1400°C, and the volume concentration of O2 in the pyrolysis atmosphere is 15%. The volume proportion of particles of the obtained positive electrode material under 6t and 1 μm is 5%, and SO4 2- The surface enrichment is high, indicating that the positive electrode material has a high content of micro powder and free SO4 2- The content of is high, resulting in poor cycle stability of the positive electrode material.
[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A positive electrode material, characterized in that: The chemical formula of the positive electrode material is Li x Ni a Co b M c N d O2, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, 0≤d≤0.10, a+b+c+d=1, the M element includes at least one of Mn or Al, and the N element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y; the free SO4 of the positive electrode material 2- The content of SO4 is ≤800ppm, and SO4 2- The surface enrichment is ≤70%.
2. The positive electrode material according to claim 1, characterized in that The volume proportion of particles of the positive electrode material below 1 μm is ≤4% under a pressure of 6T; And / or, the lattice strain of the positive electrode material is ≤0.2%.
3. The positive electrode material according to claim 1, characterized in that The positive electrode material also includes a coating layer, and the coating layer includes at least one element of Al, Ti, Zr, Y, Nb, Mg, W, B, Ce, Co, and Mn.
4. The positive electrode material according to claim 1, characterized in that The volume particle size median D50 of the positive electrode material is 2.5 μm-5 μm; And / or, the particle size Dmin of the positive electrode material is greater than 0.3 μm; And / or, the particle size Dmax of the positive electrode material is less than 14 μm.
5. The positive electrode material according to claim 1, characterized in that The specific surface area of the positive electrode material is 0.5-1.2 m 2 / g; And / or, the pH of the positive electrode material satisfies 11.0≤pH≤12.
0.
6. The positive electrode material according to claim 1, characterized in that The positive electrode material is a single crystal material, and the positive electrode material includes grains with the same orientation, and the grain size of the grains is 1 μm to 5 μm.
7. A method for preparing a positive electrode material, characterized in that: The preparation method comprises: subjecting a metal salt mixed solution containing Ni salt, Co salt, M salt and N salt to pressure atomization treatment and pyrolysis treatment in sequence to obtain the positive electrode material precursor, wherein the volume content of O2 in the pyrolysis atmosphere is ≤12%; mixing the positive electrode material precursor and a lithium source and sintering them to obtain the positive electrode material; The general formula of the positive electrode material precursor is Ni a Co b M c N d O e , wherein, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.35, 0≤d≤0.10, a+b+c+d=1, 1≤e≤1.15, M element includes at least one of Mn and Al, N element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y; The chemical formula of the positive electrode material is Li x Ni a Co b M c N d O2, wherein 0.98≤x≤1.1, 0.50≤a≤0.98, 0<b≤0.20, 0<c≤0.30, 0≤d≤0.10, a+b+c+d=1, M element includes at least one of Mn and Al; N element includes at least one of Al, Ti, Zr, Mg, Sr, Ba, Ca, Nb, W, Sb, Ta, Sn and Y; the free SO4 of the positive electrode material 2- The content of SO4 is ≤800ppm, and SO4 2- The surface enrichment is ≤70%.
8. The method for preparing the positive electrode material according to claim 7, characterized in that: In the metal salt mixed solution, the molar ratio of Ni element, Co element, M element and N element is (50-98): (0-20): (0-35): (0-0.10), and the molar ratio of Co element and M element is not 0; And / or, the Ni salt, M salt, Co salt and N salt each independently include at least one of chloride, nitrate, oxalate and acetate; And / or, in the metal salt mixed solution, the total metal concentration is 100g / L-500g / L, wherein the total metal includes Ni element, Co element, M element and N element; And / or, the pressure of the atomization treatment is 0.4MPa-0.8MPa; And / or, the pyrolysis treatment includes a first temperature zone and a second temperature zone, the temperature of the first temperature zone is 1000-1200° C., and the temperature of the second temperature zone is 500-800° C.; And / or, in the metal salt mixed solution, based on the total mass of Ni element, Co element, Mn element, and N element, SO4 2- The content is ≤2400ppm; And / or, after atomization treatment, the residence time of the material in the first temperature zone is 2 to 5 seconds.
9. The method for preparing the positive electrode material according to claim 7 or 8, characterized in that: The sintering temperature is 750-980°C, and the sintering time is 10h-30h; And / or, the sintering atmosphere is an oxygen-containing atmosphere, and the volume proportion of O2 is ≥95%; And / or, the molar ratio of the lithium element in the lithium source to the total metal in the positive electrode material precursor is 0.98-1.10; wherein the molar amount of the total metal in the positive electrode material precursor is the sum of the molar amounts of Ni element, Co element, M element and N element.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode material according to any one of claims 1 to 6 or the positive electrode material obtained by the method for preparing the positive electrode material according to any one of claims 7 to 9.
Citation Information
Patent Citations
Positive-electrode active material for non-aqueous electrolyte secondary battery, method for manufacturing positive-electrode active material for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery
CN110720152A
Modified high-nickel positive electrode material and preparation method thereof
CN114068911A
Lithium-rich positive electrode material, preparation method thereof and lithium ion battery
CN115881943A
Nonaqueous electrolyte secondary battery
JP2008270086A
Positive electrode active material for lithium secondary battery, method for producing same, and lithium secondary battery
WO2011071068A1
Cited By
Positive electrode material and lithium ion battery
CN120998995A
Positive electrode material and preparation method therefor, and lithium-ion battery
WO2026138019A1